Pengembangan Media Pembelajaran Komik Berbasis Aplikasi Comic Page Creator menggunakan Model Problem Based Learning pada Mata Pelajaran IPAS di Kelas IV Sekolah Dasar - Wulandari, Ananda Putri; Rahmatina, Rahmatina; Zahara, Leni; Hamimah, Hamimah (Asian Journal of Early Childhood and Elementary Education, 2025)
The limited use and lack of diversity in learning media are among the factors contributing to the low effectiveness of teaching and learning processes in elementary schools. This study aims to develop a comic-based instructional medium using Comic Page Creator, which has been validated and classified as both valid and practical for classroom use. The research employed a development approach using the ADDIE model, comprising five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through validation questionnaires completed by content, language, and media experts, as well as practicality questionnaires involving teachers and students. The trials were conducted with fourth-grade students at three elementary schools: SDN 12 Pagaruyung, SDN 08 Pagaruyung, and SDN 15 Pagaruyung. The validation results showed that the comic media achieved a content validity score of 78% (valid category), language validity of 90% (highly valid), and media validity of 96% (highly valid). Practicality tests showed scores of 88% from teachers and 91.86% from students, both categorized as highly practical. These findings confirm that the comic-based instructional media developed using Comic Page Creator is valid and practical, with strong potential to enhance the quality of IPAS learning in fourth-grade elementary classrooms.